2012
DOI: 10.1017/s1368980012004417
|View full text |Cite
|
Sign up to set email alerts
|

Dietary intakes of women during pregnancy in low- and middle-income countries

Abstract: Objective: To provide a better understanding of dietary intakes of pregnant women in low-and middle-income countries. Design: Systematic review was performed to identify relevant studies which reported nutrient intakes or food consumption of pregnant women in developing countries. Macronutrient and micronutrient intakes were compared by region and the FAO/WHO Estimated Average Requirements. Food consumption was summarized by region. Setting: Developing countries in Africa, Asia, and the Caribbean and Central/ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
203
1
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 225 publications
(241 citation statements)
references
References 89 publications
22
203
1
2
Order By: Relevance
“…Inadequate intake of calcium, iron and zinc among these women and the pregnant women in our study was due to the consumption of a major portion of their daily energy intake from white rice [51], which is relatively very low in calcium, iron, and zinc [29]. In addition, the dietary patterns of pregnant women in low-resource settings are characterised by a lack of diversity, with infrequent consumption of nutrient-rich foods and milk and milk products [5,55,56].…”
Section: Predictors Of Calcium Iron and Zinc Bioavailabilitymentioning
confidence: 99%
“…Inadequate intake of calcium, iron and zinc among these women and the pregnant women in our study was due to the consumption of a major portion of their daily energy intake from white rice [51], which is relatively very low in calcium, iron, and zinc [29]. In addition, the dietary patterns of pregnant women in low-resource settings are characterised by a lack of diversity, with infrequent consumption of nutrient-rich foods and milk and milk products [5,55,56].…”
Section: Predictors Of Calcium Iron and Zinc Bioavailabilitymentioning
confidence: 99%
“…To ensure adequate nutrient intake, dietary diversification has been recommended as one of the best strategies. It is particularly highly recommended among pregnant women since they have increased nutrient requirements [6,7]. Labadarios et al [8] have argued comprehensively that the more food groups included in a person's daily diet, then the greater the chances of meeting nutrient requirements.…”
Section: Introductionmentioning
confidence: 99%
“…Labadarios et al [8] have argued comprehensively that the more food groups included in a person's daily diet, then the greater the chances of meeting nutrient requirements. Additionally, many studies have demonstrated that dietary diversity is indeed associated with nutrient adequacy [6,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review including sixty-two studies published from 1989 to 2011 Lee et al reported that a large majority of pregnant women from Africa and Asia had taken lower energy and micronutrient than those recommended by Food and Agricultural Organization/World Health Organization (FAO/WHO). Lee et al concluded that the problems of unbalanced macronutrient profiles and multiple micronutrient deficiencies are common among pregnant women in developing countries across the region of the world [18].…”
Section: Introductionmentioning
confidence: 99%